Return-to-play guidelines in concussion: revisiting the literature - Sabini, R. C.; Nutini, D. N.; Nutini, M. (The Physician and Sportsmedicine, 2014)
Return-to-play (RTP) guidelines in concussion management and treatment continue to challenge clinicians, despite recent updates to the protocols and the ongoing media attention. The current guidelines address individualized treatment planning but are difficult to apply to athletes who experience prolonged symptoms, are younger, or have sustained multiple concussions. Recent literature findings have contributed to an improved understanding and applicability of the guidelines while emphasizing a multidisciplinary paradigm in formulating an individualized RTP decision. Successful implementation of the RTP guidelines will ensure that athletes are protected from further injury and return to their baseline functional status.